Contribution of the seed microbiome to weed management. (22nd July 2016) - Müller‐Stöver, D; Nybroe, O; Baraibar, B; Loddo, D; Eizenberg, H; French, K; Sønderskov, M; Neve, P; Peltzer, D A; Maczey, N; Christensen, S
Summary: Seed‐attacking microorganisms have an undefined potential for management of the weed seedbank, either directly through inundative inoculation of soils with effective pathogenic strains, or indirectly by managing soils in a manner that promotes native seed‐decaying microorganisms. However, research in this area is still limited and not consistently successful because of technological limitations in identifying the pathogens involved and their efficacy. We suggest that these limitations can now be overcome through application of new molecular techniques to identify the microorganisms interacting with weed seeds and to decipher their functionality. However, an interdisciplinary weed management approach that includes weed scientists, microbiologists, soil ecologists and molecular biologists is required to provide new insights into physical and chemical interactions between different seed species and microorganisms. Such insight is a prerequisite to identify the best candidate organisms to consider for seedbank management and to find ways to increase weed seed suppressive soil communities.